Grafémica vasco-románica. Implicaciones mutuas - Echenique Elizondo, M. Teresa (Caplletra. Revista Internacional de Filologia, 2015)
From an analysis of the graphemes in Bernart Dechepare's Linguae Vascorum Primitiae, the author shows that Basque referred to Navarrese Romance script to establish its own graphic code. She also demonstrates that this work contains valuable information for the study of the late stages of Romance of Navarre.